What's Not There: Odd Lots and Market Data - O'HARA, MAUREEN; YAO, CHEN; YE, MAO (Journal of Finance, 2014)
ABSTRACT We investigate odd‐lot trades in equity markets. Odd lots are increasingly used in algorithmic and high‐frequency trading, but are not reported to the consolidated tape or in databases such as TAQ. In our sample, the median number of odd‐lot trades is 24% but in some stocks odd lots are 60% or more of trading. Odd‐lot trades contribute 35% of price discovery, consistent with informed traders using odd lots to avoid detection. Omitting odd‐lot trades leads to inaccuracies in order imbalance measures and makes sentiment measures unreliable. Excluding odd lots from the consolidated tape raises important regulatory issues.